2011
DOI: 10.4012/dmj.2010-061
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion resistance evaluation of Pd-free Ag-Au-Pt-Cu dental alloys

Abstract: The corrosion resistance of nine experimental Pd-free Ag-Au-Pt-Cu dental alloys in a 0.9% NaCl solution was investigated using cyclic voltammetry (CV), optical microscopy, and scanning electron microscopy (SEM). CV measurements revealed that the breakdown potential (Ebd) and zero current potential (Ezc) increased with increasing Au/(Au+Ag) atomic ratio. Thus, the Au/(Au+Ag) atomic ratio, but not the Cu content, influenced the corrosion resistance of Ag-Au-Pt-Cu alloys. After the forward scan of CV, both optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Laub and Stanford [15] reported that for ternary Au-Ag-Cu alloys, both copper and silver were involved in the corrosion process; corrosion occurring primarily in the silver-rich regions and secondarily in the copper-rich regions. Fujita and co-workers [16] observed for an Ag-Au-Pt-Cu alloy, comprising of a mixture of a major phase of the matrix and minor phase of small grains embedded in the matrix, corrosion occurred preferentially in the matrix and not the precipitates. It was suggested that Ag + ions were released from the Ag-Au-rich matrix phase but not from the Pt-Cu-rich second phase.…”
Section: Introductionmentioning
confidence: 99%
“…Laub and Stanford [15] reported that for ternary Au-Ag-Cu alloys, both copper and silver were involved in the corrosion process; corrosion occurring primarily in the silver-rich regions and secondarily in the copper-rich regions. Fujita and co-workers [16] observed for an Ag-Au-Pt-Cu alloy, comprising of a mixture of a major phase of the matrix and minor phase of small grains embedded in the matrix, corrosion occurred preferentially in the matrix and not the precipitates. It was suggested that Ag + ions were released from the Ag-Au-rich matrix phase but not from the Pt-Cu-rich second phase.…”
Section: Introductionmentioning
confidence: 99%